Phase Ib study evaluating safety and clinical activity of the anti-HER3 antibody lumretuzumab combined with the anti-HER2 antibody pertuzumab and paclitaxel in HER3-positive, HER2-low metastatic breast cancer - Schneeweiss, Andreas; Park-Simon, Tjoung-Won; Albanell, Joan; Lassen, Ulrik; Cortes, Javier; Dieras, Veronique; May, Marcus; Schindler, Christoph; Marmé, Frederik; Cejalvo, Miguel Juan; Martinez-Garcia, Maria; Gonzalez, Iria; et al. (Investigational new drugs, 2018)
Purpose To investigate the safety and clinical activity of comprehensive human epidermal growth factor receptor (HER) family receptor inhibition using lumretuzumab (anti-HER3) and pertuzumab (anti-HER2) in combination with paclitaxel in patients with metastatic breast cancer (MBC). Methods This phase Ib study enrolled 35 MBC patients (first line or higher) with HER3-positive and HER2-low (immunohistochemistry 1+ to 2+ and in-situ hybridization negative) tumors. Patients received lumretuzumab (1000 mg in Cohort 1; 500 mg in Cohorts 2 and 3) plus pertuzumab (840 mg loading dose [LD] followed by 420 mg in Cohorts 1 and 2; 420 mg without LD in Cohort 3) every 3 weeks, plus paclitaxel (80 mg/m2 weekly in all cohorts). Patients in Cohort 3 received prophylactic loperamide treatment. Results Diarrhea grade 3 was a dose-limiting toxicity of Cohort 1 defining the maximum tolerated dose of lumretuzumab when given in combination with pertuzumab and paclitaxel at 500 mg every three weeks. Grade 3 diarrhea decreased from 50% (Cohort 2) to 30.8% (Cohort 3) with prophylactic loperamide administration and omission of the pertuzumab LD, nonetheless, all patients still experienced diarrhea. In first-line MBC patients, the objective response rate in Cohorts 2 and 3 was 55% and 38.5%, respectively. No relationship between HER2 and HER3 expression or somatic mutations and clinical response was observed. Conclusions Combination treatment with lumretuzumab, pertuzumab and paclitaxel was associated with a high incidence of diarrhea. Despite the efforts to alter dosing, the therapeutic window remained too narrow to warrant further clinical development. Trial registration: on ClinicalTrials.govwith the identifier NCT01918254 first registered on 3rd July 2013.